Developing a work roll model by analyzing the mechanism influence through analytic calculation - Hussein, Mohammed Ali (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a novel approach to developing a work roll prediction model that takes into account both the mechanism and condition influences on work roll wear. This was accomplished by conducting an analytic calculation of work roll mechanism influence, constructing a work roll wear model, and combining the wear mechanism with actual wear data.
Keywords: wear; mechanism; developing model; work roll